Pemerkasaan Pengajian Al-Qur’an di Perguruan Tinggi Agama Islam (Ptai) di Indonesia: Kajian di Institut Ilmu Al-Qur’an (Iiq) Jakarta: Empowerment of Quranic Studies in Islamic Higher Education Institutions (PTAI) in Indonesia: A Study at the Institute of Quranic Sciences (IIQ) Jakarta - Achmad, Nurjanah; Abdullah, Mustaffa; Mohd Adnan, Mohamad Azrien (Al-Basirah Journal, 2022)
Until now, the study of the Qur'an in Indonesian Islamic Religious Universities (PTAI) has remained monotonous and unchanging. Furthermore, the study of the Qur'an faces a number of challenges, including the continued use of classic books, traditional teaching methods, limited technology, and less professional educators. Meanwhile, the world is in desperate need of solutions to the ummah's increasingly complex problems. Following that, the researchers proposed that the Institute of Qur'anic Science (IIQ) in Jakarta, Indonesia, be strengthened as a specialised institution in the field of Qur'anic science that is well known in Indonesia. A qualitative approach is used in this study. Structured interviews were used as the primary method of data collection, and they were supplemented by relevant important documents. Thematic analysis methods were used in the data analysis process. According to the study's findings, the empowerment of Qur'anic studies in IIQ is implemented in four dimensions: curriculum and syllabus evaluation, strengthening teaching methods, utilising and developing ICT, and improving teaching staff professionalism. It is hoped that this will help to establish IIQ as an authoritative reference centre in the study of Qur'anic knowledge, as well as to perform transformation to achieve excellence in its 50th year. It can also be used as a reference by other IPTA or IPTS in Indonesia or Malaysia to take additional steps to strengthen the field of Qur'anic studies and bring it up to par with other mainstream education fields.